Developing Skills for Youthful Leaders Module 3: Being Your Best Archival - Elizabeth B. Bolton; John R. Rutledge; Linda Bowman; Linda Barber (EDIS)
The objective of this lesson are to identify your own unique personality traits, to accept both compliments and criticism from others in a positive way, to choose one trait to work toward improving and develop a specific plan for improvement, to recognize that you must take risks in order to grow and develop, and to learn to value yourself. This document is FCS9090, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. EDIS publication date May 2006. Reviewed July 2009.